48x-24+48-9x=24x+56

Simple and best practice solution for 48x-24+48-9x=24x+56 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 48x-24+48-9x=24x+56 equation:


Simplifying
48x + -24 + 48 + -9x = 24x + 56

Reorder the terms:
-24 + 48 + 48x + -9x = 24x + 56

Combine like terms: -24 + 48 = 24
24 + 48x + -9x = 24x + 56

Combine like terms: 48x + -9x = 39x
24 + 39x = 24x + 56

Reorder the terms:
24 + 39x = 56 + 24x

Solving
24 + 39x = 56 + 24x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24x' to each side of the equation.
24 + 39x + -24x = 56 + 24x + -24x

Combine like terms: 39x + -24x = 15x
24 + 15x = 56 + 24x + -24x

Combine like terms: 24x + -24x = 0
24 + 15x = 56 + 0
24 + 15x = 56

Add '-24' to each side of the equation.
24 + -24 + 15x = 56 + -24

Combine like terms: 24 + -24 = 0
0 + 15x = 56 + -24
15x = 56 + -24

Combine like terms: 56 + -24 = 32
15x = 32

Divide each side by '15'.
x = 2.133333333

Simplifying
x = 2.133333333

See similar equations:

| -4.8(x-3.25)=14.4 | | -4(5y+3)+5(1+4y)=0 | | 15+0.35x=30+0.30x | | 8x-24+4x=-19 | | -10+9p=44 | | (3x+3)(X+3)=-1 | | ln(8x^5)=ln(5x)+3 | | 9(5+v)=-90 | | -4=-9+w | | -100+(-77)= | | 2x+x+4x= | | F(x)=x^4-4x^3+16 | | -12x^2+19x-22=0 | | 63-2x=70 | | 30=x-.25x | | -3x-5x=2x+10 | | -25x+25=75 | | 8+5c+5= | | 0=40+15t-4.9t^2 | | 0.4=0.08 | | 2a*(-3a^2)= | | 3+9x=-6 | | 8x+1=7-1x | | 15-0.06x=5 | | 4+17x-3=9x+31-7x | | 3x-4=56-9x | | 9x+13=-8 | | 10x+3=4x+39 | | 3,570=34(p+30) | | 90=30x | | 6n^3-4n^2= | | 6m^2-23m-18=0 |

Equations solver categories